2019
DOI: 10.1002/jobm.201800674
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, identification, and characterization of diesel‐oil‐degrading bacterial strains indigenous to Changqing oil field, China

Abstract: In the present study, 12 indigenous diesel‐oil‐degrading bacteria were isolated from the petroleum‐contaminated soils of the Changqing oil field (Xi’an, China). Measurement of the diesel‐oil degradation rates of these strains by the gravimetric method revealed that they ranged from 42% to 66% within 2 weeks. The highest degradation rates were observed from strains CQ8‐1 (66%), CQ8‐2 (62.6%), and CQ11 (59%), which were identified as Bacillus thuringiensis, Ochrobactrum anthropi, and Bordetella bronchialis, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The results in this study indicated that the growth rates of the two strains reflected diesel oil degradation trends. These results were in good agreement with those of previous studies conducted by Sun et al (2019). Besides that, the growth of the bacteria during the incubation time because of the accumulate of many compounds from the diesel oil itself for storage as a strategy to survive in variable environments.…”
Section: Enumeration Of Bacteria Using Colonysupporting
confidence: 92%
See 1 more Smart Citation
“…The results in this study indicated that the growth rates of the two strains reflected diesel oil degradation trends. These results were in good agreement with those of previous studies conducted by Sun et al (2019). Besides that, the growth of the bacteria during the incubation time because of the accumulate of many compounds from the diesel oil itself for storage as a strategy to survive in variable environments.…”
Section: Enumeration Of Bacteria Using Colonysupporting
confidence: 92%
“…It was found that strain AQ5-06 achieved 37.5% diesel degradation, while strain AQ5-05 achieved 34.5%. In comparison, Sun et al (2019) showed about 42% to 66% degradation within two weeks. These results were quite similar to this study.…”
Section: Diesel Oil Degradation Using Gravimetric Analysismentioning
confidence: 87%
“…Biodegradation, as a form of bioremediation, is costeffective, efficient, safe and eco-friendly [10]. It employs different organisms such as fungi, algae and bacteria, or their products (enzymes and biomolecules) to degrade petroleum products.…”
Section: Introductionmentioning
confidence: 99%
“…However, bioremediation is recognized as an effective method for the treatment of oil contaminated areas (Zhang et al 2014). Bioremediation technology utilizes microorganisms and their activities to degrade toxic pollutants to harmless products with the aim of lowering costs, and environmental safety with absence of secondary pollutants (Philip et al 2005;Sun et al 2019). Biodegradation of diesel oil by microorganisms had been widely demonstrated by the use of several species of the following genera, to cite some, Bacillus, Pseudomonas, Sphingomonas, Acinetobacter, Serratia, Citrobacter, Raoultella, Stenotrophomonas mainly isolated from a wide diversity of oil-contaminated soils (Leahy and Colwell 1990;Morales-Guzm an et al 2017;Palanisamy et al 2014;Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Various salt-tolerant hydrocarbondegrading bacteria from different genera (either saline tolerant ones (e.g., Marinobacter, Halomonas, Alcanivorax, Haloferax, Haloarcula, or Ochrobactrum anthropi) or generalist ones (e.g., Bacillus thuringiensis, Bordetella bronchialis and Pseudomonas sp. CQ2), have been isolated from hypersaline oil reservoirs, saline oilfield-produced water, and high-salinity hydrocarbon impacted environments (Fathepure 2014;Kebbouche-Gana et al 2009;Sun et al 2018;Sun et al 2019). In oil industry, the isolation of microorganisms that degrades hydrocarbons in highly saline milieus is of great importance for effective wastewater treatment strategies in refineries, oil terminals, and depots (Riis et al 2003).…”
Section: Introductionmentioning
confidence: 99%